On the units of integral group ring of Cn × C₆ - Küsmüş, Ö. (Algebra and Discrete Mathematics, 2015)
There are many kind of open problems withvarying difficulty on units in a given integral group ring. In thisnote, we characterize the unit group of the integral group ring of Cn × C₆ where Cn = 〈a: aⁿ = 1〉 and C₆ = 〈x: x⁶ = 1〉. We show that U₁(Z[Cn × C₆]) can be expressed in terms of its 4 subgroups. Furthermore, forms of units in these subgroups are described by the unit group U₁(ZCn).